The Dynamics of Tobin’s Q - Puopolo, Giovanni W. (Review of Finance, 2017)
Abstract In this article, I propose a general-equilibrium model with proportional adjustment costs and industry-specific capital to study the firm migration phenomenon across market-to-book ratio. In my model, investors’ desire to diversify their portfolios and investment frictions generate a mean-reverting dynamics of Tobin’s q consistent with the probabilities of migration found in the data, and a non-linear pattern in the conditional volatility of Tobin’s q. In addition, since firms’ market-to-book ratios are function of the state of the economy and contain information about stock returns, stock prices inherit these properties, yielding asset-pricing implications in line with the empirical evidence, namely the value premium and a non-monotone relationship between the volatility of stock returns and the Tobin’s q.